Deception Behavior dalam Perspektif Kajian Al-Qur’an dan Hadis - Maryam, Siti; Mahmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Social media has a significant impact on people's lives in various aspects, from lifestyle to standards of attractiveness and beauty. Consequently, social media users often strive to present an appealing self-image that differs from reality, a phenomenon referred to in psychological studies as Deception Behavior. The motives for this behavior vary, including entertainment, the desire for higher social status, or even deceit. This study will examine several forms of deception behavior from the perspective of the Qur’an and Hadith. The research method used is library research, which involves collecting data by understanding and studying theories from various literature sources such as books, journals, articles, and previous research studies. The results indicate that some forms of deception behavior on social media involve elements of dishonesty that contradict religious teachings (Q.S. An-Nahl [16]: 105), such as concealing one’s true identity with fake accounts used for hate speech (Q.S. Al-Hujurat [49]: 12), self-branding for fraudulent purposes (Q.S. Al-Baqarah [2]:9), flexing behavior that contains elements of showing off and arrogance (Q.S. Luqman [31]: 18), and excessive, manipulative use of filters that can deceive others (Q.S. Al-Baqarah [2]: 42).